Pendidikan Karakter Pada Generasi Alpha di Era Digital - Ani Oktarina; Emi Fahrudi; Moh. Mundzir (Alzam: Journal of Islamic Early Childhood Education, 2024)
Education is important for everyone without exception. Education is something human learning in the form of knowledge, skills and knowledge which aims to facilitate human understanding and change a person's attitudes and style. Therefore, this research was conducted to determine the character education of Alpha generation children in an increasingly digital era. One of them is that the education industry also has the prerequisites to develop towards digital life. Therefore, this also affects the development of the child's personality. Therefore, the results of this research are that children's personalities adapt to digital conditions and developments, especially in the field of education.